The Death of Ivan Ilyich & Other Stories - Tolstoy, Leo (Wordsworth Editions Ltd, 2004)
In the early story Family Happiness, Tolstoy explores courtship and marriage from the point of view of a young wife. In The Kreutzer Sonata he gives us a terrifying study of marital breakdown, in The Devil a powerful depiction of the power of sexual temptation, and, in perhaps the finest of all, The Death of Ivan Ilyich, he portrays the long agony of a man gradually coming to terms with his own mortality.
Keywords: Classic; Fiction